The entrepreneurship of survival among urban adults experiencing homelessness and mental illness. Issue 6 (18th June 2019) - Isaak, Corinne A.; Reynolds, Kristin; Sareen, Jitender; Distasio, Jino
Abstract: Aims: Using an entrepreneurship lens, this study examined the narratives of urban adults experiencing homelessness and living with mental illness, to explore strategies used for day‐to‐day survival. Methods: Semi‐structured qualitative interviews were conducted with 14 females, 30 males, and one individual identifying as "other, " living in a mid‐sized Canadian city. The average age was 39 years. Data were transcribed verbatim and analyzed using thematic analysis informed by grounded theory. Findings: Participants described creative and intentional strategies for managing life on the street without permanent shelter, including recognition of opportunities, mobilization of their own or acquired resources, and use of social connections and communication skills, and strategies that demonstrated entrepreneurial processes. Conclusions: Findings suggest that participants used survival entrepreneurship strategies and processes to navigate daily life while experiencing homelessness. Recognition and validation of the propensity for enterprise and self‐sufficiency are central for both individual recovery and ending homelessness within similar populations.